Effectiveness of a twelve-week manual therapy intervention for shoulder injury prevention and management in female volleyball players - Tamilarasu Thenmozhi; Murugan Senthil Kumar; Yuliya Kalmykova; Swamynathan Sanjaykumar; Daria Okun (Фізична реабілітація та рекреаційно-оздоровчі технології)
Purpose: This study aimed to assess the efficacy of a twelve-week manual therapy intervention in preventing and managing shoulder injuries among female volleyball players through a randomized controlled trial.